A high heat generation and low gas generation patch material
By using a high-heat and low-gas-generating subsidy material in the steel casting process, the problems of traditional subsidy materials with low calorific value, large gas generation, and insufficient compressive strength are solved, achieving a more efficient casting feeding effect and better Compression resistance.
Patent Information
- Application Number
- CN202411448011.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-17
AI Technical Summary
In traditional casting steel technology, the subsidized materials have low heating value, large gas production capacity, and insufficient compressive strength at room temperature, which makes it difficult to effectively solve the internal shrinkage and shrinkage hole defects of the castings.
Using a high-heat and low-gas subsidy material, the raw materials include aluminum powder, iron oxide, alumina, silica, graphene, hollow glass beads, mullite powder, curing agent and binder, through a specific weight The ratio and preparation method improve the heating performance and compressive strength of the material.
It achieves the effect of high heat generation and low gas generation, significantly improves the normal temperature compressive strength of the subsidized material, and improves the shrinkage and cavity defects inside the casting.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the field of casting technology, and in particular to a high-heat-generation and low-gas-generation patching material. Background Art
[0002] Shrinkage and shrinkage defects inside castings are common problems in the steel casting process. These defects not only affect the quality of castings, but may also cause leakage, breakage and other problems in the castings during use. At present, in the steel casting process, it is usually necessary to add a thermal subsidy of equal wall thickness to the outer channel position, and adopt the thermal subsidy process technology to eliminate or reduce the shrinkage and shrinkage defects inside the castings. In addition, the traditional subsidy materials have a low calorific value, a large gas emission, and an unstable heating effect. At the same time, the gas generated during the solidification process of the casting cannot be discharged in time, which seriously affects the shrinkage compensation efficiency and the production qualification rate of the casting. In addition, the room temperature compressive strength of the subsidy material has a direct and important impact on the quality of the casting, while the room temperature compressive strength of the traditional subsidy material is insufficient. During the casting process, it may break due to the inability to withstand thermal and mechanical stresses, resulting in poor shrinkage compensation effect. Therefore, the development of a subsidy material with high heat generation, low gas emission, and high room temperature compressive strength is of great significance for improving the shrinkage and shrinkage defects inside the castings during the steel casting process. Summary of the invention
[0003] The present invention proposes a high-heat-emission and low-gas-emission patching material, which solves the problems of low calorific value, high gas-emission and low compressive strength at room temperature of the patching material in the related art.
[0004] The technical solution of the present invention is as follows:
[0005] The present invention provides a high-heat-generating and low-gas-generating patch material, the raw materials of which include the following components in parts by weight:
[0006] 40-70 parts of aluminum powder, 20-30 parts of iron oxide, 15-20 parts of aluminum oxide, 4-16 parts of silicon dioxide, 0.5-2 parts of graphene, 2-16 parts of hollow glass microspheres, 15-30 parts of mullite powder, 2-4 parts of curing agent, and 8-18 parts of binder;
[0007] The binder includes magnesium fluorosilicate, phenolic resin and carboxymethyl cellulose.
[0008] As a further technical solution, the weight ratio of the magnesium fluorosilicate, the phenolic resin and the carboxymethyl cellulose is 2-6:1:1.
[0009] When the weight ratio of magnesium fluorosilicate, phenolic resin and carboxymethyl cellulose is 2~6:1:1, the room temperature compressive strength of the patch material can be further improved.
[0010] As a further technical solution, the mullite powder is modified mullite powder.
[0011] As a further technical solution, the modified mullite powder is obtained by modifying mullite powder with vermiculite and calcium hexaaluminate.
[0012] Although mullite powder can improve the room temperature compressive strength of the patch material, the room temperature compressive strength of the patch material will decrease after continuous use. The inventors found that by modifying the mullite powder with vermiculite and calcium hexaaluminate, the room temperature compressive strength of the mullite powder can be further improved, so that the patch material still has good mechanical properties after continuous use for 24 hours.
[0013] As a further technical solution, the preparation method of the modified mullite powder comprises the following steps: blending the mullite powder, the vermiculite and the calcium hexaaluminate, calcining and grinding to obtain the modified mullite powder.
[0014] As a further technical solution, the weight ratio of the mullite powder, the vermiculite and the calcium hexaaluminate is 7-17:1:2.
[0015] When the weight ratio of mullite powder, vermiculite and calcium hexaaluminate is 7-17:1:2, the room temperature compressive strength of the patch material can be further improved.
[0016] As a further technical solution, the particle size of the mullite powder is 48-75 μm; the particle size of the vermiculite is 15-44 μm; and the particle size of the calcium hexaaluminate is 15-44 μm.
[0017] As a further technical solution, during the calcination, the temperature is 1600-1700° C. and the time is 1-2 hours.
[0018] As a further technical solution, the weight ratio of the modified mullite powder to the hollow glass microspheres is 1-3:1.
[0019] When the weight ratio of modified mullite powder to hollow glass microspheres is 1-3:1, the room temperature compressive strength of the patch material can be further improved.
[0020] As a further technical solution, the curing agent is one or two of hexamethylenetetramine and tetrachlorophthalic anhydride.
[0021] The present invention also provides a method for preparing a high-heat-generating, low-gassing patch material, comprising the following steps: mixing the components in parts by weight, putting into a mold, curing, and forming to obtain the high-heat-generating, low-gassing patch material.
[0022] As a further technical solution, during the curing, the temperature is 160-200° C. and the time is 20-40 minutes.
[0023] The working principle and beneficial effects of the present invention are:
[0024] In the present invention, the patch material has the advantages of high heat generation, low gas generation, and easy falling off after casting. The binder in the patch material includes magnesium fluorosilicate, phenolic resin and carboxymethyl cellulose. Through the synergistic effect of the organic binder and the inorganic binder, it helps to better combine other raw materials in the patch material, thereby improving the internal tightness of the patch material, and then significantly improving the room-temperature compressive strength of the patch material. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In the following embodiments and comparative examples, the particle size of aluminum powder is 74 μm; the particle size of iron oxide is 44 μm; the particle size of aluminum oxide is 0.3 μm; the particle size of silicon dioxide is 20 nm; the particle size of graphene is 9 nm; the particle size of hollow glass microspheres is 80 μm and the wall thickness is 2 μm; the particle size of mullite powder is 48 μm; the particle size of vermiculite is 15 μm; the particle size of calcium hexaaluminate is 15 μm; the purity of magnesium fluorosilicate is 98.5%; the model of phenolic resin is BF01; the viscosity of carboxymethyl cellulose is 1400 and the CAS number is 9000-11-7.
[0027] Example 1
[0028] A high-heat-generating and low-gassing patch material, the raw materials of which include the following components in parts by weight:
[0029] 40 parts of aluminum powder, 20 parts of iron oxide, 15 parts of aluminum oxide, 4 parts of silicon dioxide, 0.5 parts of graphene, 2 parts of hollow glass microspheres, 15 parts of mullite powder, 2 parts of tetrachlorophthalic anhydride, and 8 parts of binder;
[0030] The binder includes 3 parts of magnesium fluorosilicate, 2.5 parts of phenolic resin and 2.5 parts of carboxymethyl cellulose;
[0031] The preparation method comprises the following steps: stirring and mixing the above components in parts by weight, putting into a mold, curing at 160° C. for 40 minutes, and forming to obtain a high-heat-generating and low-gassing patch material.
[0032] Example 2
[0033] A high-heat-generating and low-gassing patch material, the raw materials of which include the following components in parts by weight:
[0034] 55 parts of aluminum powder, 25 parts of iron oxide, 18 parts of aluminum oxide, 10 parts of silicon dioxide, 1.5 parts of graphene, 4 parts of hollow glass microspheres, 20 parts of mullite powder, 3 parts of tetrachlorophthalic anhydride, and 16 parts of binder;
[0035] The binder includes 7 parts of magnesium fluorosilicate, 4.5 parts of phenolic resin and 4.5 parts of carboxymethyl cellulose;
[0036] The preparation method comprises the following steps: mixing the above components in parts by weight, putting into a mold, curing at 180° C. for 30 minutes, and forming to obtain a high-heat-generating and low-gassing patch material.
[0037] Example 3
[0038] A high-heat-generating and low-gassing patch material, the raw materials of which include the following components in parts by weight:
[0039] 70 parts of aluminum powder, 30 parts of iron oxide, 20 parts of aluminum oxide, 16 parts of silicon dioxide, 2 parts of graphene, 16 parts of hollow glass microspheres, 30 parts of mullite powder, 4 parts of tetrachlorophthalic anhydride, and 18 parts of binder;
[0040] The binder includes 8 parts of magnesium fluorosilicate, 5 parts of phenolic resin and 5 parts of carboxymethyl cellulose;
[0041] The preparation method comprises the following steps: stirring and mixing the above components in parts by weight, putting them into a mold, curing them at 200° C. for 20 minutes, and forming them to obtain a high-heat-generating and low-gassing patch material.
[0042] Example 4
[0043] The only difference between this embodiment and embodiment 2 is that in this embodiment, the binder includes 13 parts of magnesium fluorosilicate, 1.5 parts of phenolic resin and 1.5 parts of carboxymethyl cellulose.
[0044] Example 5
[0045] The only difference between this embodiment and embodiment 2 is that in this embodiment, the binder includes 8 parts of magnesium fluorosilicate, 4 parts of phenolic resin and 4 parts of carboxymethyl cellulose.
[0046] Example 6
[0047] The only difference between this embodiment and embodiment 2 is that in this embodiment, the binder includes 12 parts of magnesium fluorosilicate, 2 parts of phenolic resin and 2 parts of carboxymethyl cellulose.
[0048] Example 7
[0049] The only difference between this embodiment and embodiment 6 is that, in this embodiment, the mullite powder is modified mullite powder, and the modified mullite powder is obtained by modifying mullite powder with vermiculite. The preparation method of the modified mullite powder comprises the following steps: blending 17 parts of mullite powder and 3 parts of vermiculite, calcining at 1650°C for 1.5h, and grinding to obtain modified mullite powder.
[0050] Example 8
[0051] The only difference between this embodiment and embodiment 6 is that in this embodiment, the mullite powder is modified mullite powder, and the modified mullite powder is obtained by modifying mullite powder with calcium hexaaluminate. The preparation method of the modified mullite powder includes the following steps: blending 17 parts of mullite powder and 3 parts of calcium hexaaluminate, calcining at 1650°C for 1.5 hours, and grinding to obtain modified mullite powder.
[0052] Example 9
[0053] The only difference between this embodiment and embodiment 6 is that, in this embodiment, the mullite powder is modified mullite powder, and the modified mullite powder is obtained by modifying mullite powder with vermiculite and calcium hexaaluminate. The preparation method of the modified mullite powder comprises the following steps: blending 11 parts of mullite powder, 3 parts of vermiculite and 6 parts of calcium hexaaluminate, calcining at 1650°C for 1.5 hours, and grinding to obtain modified mullite powder.
[0054] Example 10
[0055] The only difference between this embodiment and embodiment 9 is that in this embodiment, 18.5 parts of mullite powder, 0.5 parts of vermiculite and 1 part of calcium hexaaluminate are added.
[0056] Embodiment 11
[0057] The only difference between this embodiment and embodiment 9 is that in this embodiment, 14 parts of mullite powder, 2 parts of vermiculite and 4 parts of calcium hexaaluminate are added.
[0058] Example 12
[0059] The only difference between this embodiment and embodiment 9 is that in this embodiment, 17 parts of mullite powder, 1 part of vermiculite and 2 parts of calcium hexaaluminate are added.
[0060] Example 13
[0061] The only difference between this embodiment and embodiment 11 is that in this embodiment, 14 parts of hollow glass microspheres and 10 parts of modified mullite powder are added (in the modified mullite powder, the weight ratio of mullite powder, vermiculite and calcium hexaaluminate is 7:1:2).
[0062] Embodiment 14
[0063] The only difference between this embodiment and embodiment 11 is that in this embodiment, 4 parts of hollow glass microspheres and 20 parts of modified mullite powder are added (in the modified mullite powder, the weight ratio of mullite powder, vermiculite and calcium hexaaluminate is 7:1:2).
[0064] Embodiment 15
[0065] The only difference between this embodiment and embodiment 11 is that in this embodiment, 12 parts of hollow glass microspheres and 12 parts of modified mullite powder are added (in the modified mullite powder, the weight ratio of mullite powder, vermiculite and calcium hexaaluminate is 7:1:2).
[0066] Example 16
[0067] The only difference between this embodiment and embodiment 11 is that in this embodiment, 6 parts of hollow glass microspheres and 18 parts of modified mullite powder are added (in the modified mullite powder, the weight ratio of mullite powder, vermiculite and calcium hexaaluminate is 7:1:2).
[0068] Comparative Example 1
[0069] The difference between this comparative example and Example 1 is that in this comparative example, no carboxymethyl cellulose is added, 3 parts of magnesium fluorosilicate are added, and 5 parts of phenolic resin are added.
[0070] Comparative Example 2
[0071] The difference between this comparative example and Example 1 is that in this comparative example, no phenolic resin is added, 3 parts of magnesium fluorosilicate are added, and 5 parts of carboxymethyl cellulose are added.
[0072] Comparative Example 3
[0073] The difference between this comparative example and Example 1 is that in this comparative example, magnesium fluorosilicate is not added, 4 parts of phenolic resin and 4 parts of carboxymethyl cellulose are added.
[0074] Comparative Example 4
[0075] The difference between this comparative example and Example 1 is that in this comparative example, no carboxymethyl cellulose and no phenolic resin are added, and 8 parts of magnesium fluorosilicate are added.
[0076] Experimental Example 1
[0077] The gas emission of the patch materials prepared in Examples 1 to 3 was measured using an intelligent casting molding material gas emission tester (model SZ-CET-2000). The test result was the average value of the three samples. The sample size was 50 mm × 50 mm × 100 mm. The test results are shown in Table 1 below.
[0078] Experimental Example 2
[0079] The calorific value of the patch material prepared in Examples 1 to 3 was measured using a fully automatic calorimeter (model: ZDHW-HN7000), and the test result was the average value of 3 samples; wherein the sample size was 50 mm×50 mm×100 mm; the test results are shown in Table 1 below.
[0080] Table 1 Gas generation and calorific value test results
[0081]
[0082] In Table 1, the gas emission of the patch materials prepared in Examples 1 to 3 is ≤10 mL / g, and the calorific value is ≥55000 KJ / kg, indicating that the patch materials have low gas emission and high calorific value, which can meet the requirements of the thermal patching process technology for the gas emission and calorific value of the patch materials.
[0083] Experimental Example 3
[0084] The patch materials prepared in Examples 1 to 16 and Comparative Examples 1 to 4 were tested for room temperature compressive strength using a SWY-2 digital hydraulic universal testing machine 6 h, 12 h and 24 h after preparation, respectively, wherein the test rate was 0.002 mm / min and the sample size was 50 mm×50 mm×100 mm.
[0085] The test results are shown in Table 2 below:
[0086] Table 2 Test results of compressive strength at room temperature
[0087]
[0088] Compared with Comparative Examples 1 to 4, the room-temperature compressive strength of the patch material in Example 1 is significantly improved 6h, 12h and 24h after preparation, indicating that magnesium fluorosilicate, phenolic resin and carboxymethyl cellulose have a synergistic effect, which helps to improve the compactness inside the patch material, thereby improving the room-temperature compressive strength of the patch material.
[0089] Compared with Examples 2 and 4, the room temperature compressive strength of the patch materials of Examples 5-6 is improved after 6h, 12h and 24h of preparation, indicating that when the weight ratio of magnesium fluorosilicate, phenolic resin and carboxymethyl cellulose is 2-6:1:1, the room temperature compressive strength of the patch materials can be further improved. Compared with Examples 6-8, the room temperature compressive strength of the patch materials of Examples 9-12 is improved after 6h, 12h and 24h of preparation, indicating that the room temperature compressive strength of the patch materials can be further improved by modifying the mullite powder with vermiculite and calcium hexaaluminate. Compared with Examples 9-10, the room temperature compressive strength of the patch materials of Examples 11-12 is improved after 6h, 12h and 24h of preparation, indicating that when the weight ratio of mullite powder, vermiculite and calcium hexaaluminate is 7-17:1:2, the room temperature compressive strength of the patch materials can be further improved. In addition, compared with Example 11, the room temperature compressive strength of the patch materials of Examples 13 to 16 is improved after 6h, 12h and 24h of preparation, indicating that the modified mullite powder and hollow glass microspheres have a synergistic effect and can further improve the room temperature compressive strength of the patch materials. Compared with Examples 13 to 14, the room temperature compressive strength of the patch materials of Examples 15 to 16 is improved after 6h, 12h and 24h of preparation, indicating that when the weight ratio of modified mullite powder to hollow glass microspheres is 1 to 3:1, the room temperature compressive strength of the patch materials can be further improved.
[0090] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high heat generation and low gas generation patch material, characterized in that: The raw materials consist of the following components in parts by weight: 40-70 parts of aluminum powder, 20-30 parts of iron oxide, 15-20 parts of aluminum oxide, 4-16 parts of silicon dioxide, 0.5-2 parts of graphene, 2-16 parts of hollow glass microspheres, 15-30 parts of mullite powder, 2-4 parts of curing agent, and 8-18 parts of binder; The binder is magnesium fluorosilicate, phenolic resin and carboxymethyl cellulose; The mullite powder is modified mullite powder; The modified mullite powder is obtained by modifying mullite powder with vermiculite and calcium hexaaluminate; The weight ratio of the magnesium fluorosilicate, phenolic resin and carboxymethyl cellulose is 2-6:1:1; The preparation method of the modified mullite powder comprises the following steps: blending the mullite powder, the vermiculite and the calcium hexaaluminate, calcining and grinding to obtain the modified mullite powder; The weight ratio of the mullite powder, the vermiculite and the calcium hexaaluminate is 7-17:1:2; During the calcination, the temperature is 1600-1700° C. and the time is 1-2 hours.
2. A high heat generation and low gas generation patch material according to claim 1, characterized in that: The particle size of the mullite powder is 48-75 μm; the particle size of the vermiculite is 15-44 μm; and the particle size of the calcium hexaaluminate is 15-44 μm.
3. The high heat generation and low gas generation patch material according to claim 1, characterized in that: The weight ratio of the modified mullite powder to the hollow glass microspheres is 1-3:
1.
4. The high heat generation and low gas generation patch material according to claim 1, characterized in that: The curing agent is one or two of hexamethylenetetramine and tetrachlorophthalic anhydride.
Citation Information
Patent Citations
Inorganic heat-preservation composite slurry
CN103739265A
Heating and heat-insulating filling liner
CN106699198A
Amorphous heating patch for casting and preparation method thereof
CN111451484A
Preparation method of reusable heat to preservation cap mouth
CN112851381A